ANALISIS PELAKSANAAN FUNGSI BADAN PERMUSYAWARATAN DESA (BPD) DALAM PENGAWASAN PEMBANGUNAN DI DESA BULAGIDUN TANJUNG KECAMATAN GADUNG KABUPATEN BUOL - Dunggio, Rusli (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2023)
The aim of this research is to determine and analyze the implementation of the function of the village consultative body in monitoring development in Bulagidun Tanjung village, Gadung district, Buol district. This research used descriptive qualitative methods. The research location was carried out in Bulagidun Tanjung Village, Gadung District, Buol Regency. The data sources used are primary data and secondary data, with data collection techniques through observation, interviews and documentation. The results of the research show that the function of the village consultative body in supervising development in Bulagidun Tanjung Village, Gadung District, Buol Regency has been realized well in terms of the function of the BPD which has accommodated and conveyed community aspirations as well as overseeing policies that have been implemented by the Village government as well as discussing and approving the revenue and budget, village shopping.